2015
DOI: 10.9789/2175-5361.2015.v7i3.2707-2716
|View full text |Cite
|
Sign up to set email alerts
|

Practice and knowledge of nurses about child autism

Abstract: Objective: assessing the knowledge and practice of nurses of the Family Health Strategy about autistic disorder. Method: an exploratory research of a qualitative approach consisting of 15 nurses. There was used a semistructured interview. Data analysis was made by the representational analysis. It was approved by the Committee of Ethics in Research of the University of Rio Grande do Norte (CEP/UERN nº 124/11). Results: it became evident insecurity and fragility in nurses' knowledge about autistic disorder, bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0
21

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 5 publications
1
8
0
21
Order By: Relevance
“…Por lo tanto, se excluyeron 43 publicaciones, quedaron 9 artículos para ser leído en su totalidad, de los cuales 4 no cumplían los objetivos de este estudio y, por lo tanto, sólo 5 fueron incluidos en el examen integrador, tal y como se muestra en la figura 1. (12) Práctica y el conocimiento de las enfermeras en el autismo infantil Análisis de la práctica y conocimiento del personal de enfermería de la estrategia de salud de la familia acerca del trastorno autista.…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Por lo tanto, se excluyeron 43 publicaciones, quedaron 9 artículos para ser leído en su totalidad, de los cuales 4 no cumplían los objetivos de este estudio y, por lo tanto, sólo 5 fueron incluidos en el examen integrador, tal y como se muestra en la figura 1. (12) Práctica y el conocimiento de las enfermeras en el autismo infantil Análisis de la práctica y conocimiento del personal de enfermería de la estrategia de salud de la familia acerca del trastorno autista.…”
Section: Resultsunclassified
“…En este sentido, es necesario leer las líneas, mirar más allá de lo que es visible a los ojos, porque el hecho de saber cómo cuidar implica preocuparse, mirar al otro, esta es la esencia de la vida humana. De esta manera, la atención brindada por un equipo multiprofesional debería tener el objetivo de un cuidado cualificado por medio de directrices a las familias acerca del autismo y creación de planes terapéuticos que atiendan a la singularidad de cada niño o paciente, esta asistencia puede proporcionar una mejor calidad de vida para todos los involucrados (12) .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…However, it is important that nurses and the nursing team are involved in the entire process of diagnosis and interventions for children with ASD since these professionals are at the forefront of care and are the gateway to health services [11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…[ 4 ] It is identified that nurses have inadequate knowledge about ASD screening practices and this might be a major barrier to do early identification and interventions. [ 5 ] Thus, improving nurse's understanding, knowledge, and skill regarding screening and early identification of the children with ASD is essential.…”
mentioning
confidence: 99%